PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS PELANGGAN PADA TOKO HANDPHONE ADINK CELL DI ASEMBAGUS DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Fardian, Fardian; Soeliha, Siti; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of Service Quality and Promotion on Customer Loyalty at the Adink Cell Mobile Shop in Asembagus with Consumer Satisfaction as an Intervening Variable. The population in this study are consumers who buy and use goods that have been purchased at the Adink Cell Mobile shop in Asembagus. Random sampling method (simple probability sampling) without regard to strata in the population in this study. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLSSEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that service quality has a significant effect on consumer satisfaction. Promotion has a significant effect on consumer satisfaction. Service Quality has a significant effect on Customer Loyalty. Promotion has a significant effect on customer loyalty. Consumer Satisfaction has a significant effect on Customer Loyalty. Service Quality has a significant effect on Customer Loyalty through Consumer Satisfaction. Promotion has a significant effect on Customer Loyalty through Consumer Satisfaction